Regional differences in rainfed white corn production in Mexico - González-Cruz, Jorge Luis; Torres-Rojo, Juan Manuel (Revista Mexicana de Ciencias Agrícolas, 2024)
This research aims to identify the functional form that best represents the production of rainfed white corn in Mexico. Two variants of the constant elasticity of substitution function and the Cobb-Douglas function were tested using a cross-sectional sample of 10 924 corn farmers obtained from the ‘questionnaire to collect the 2008 baseline: SAGARPA programs’. The analysis was performed at national and regional levels using fourteen factors of production. The results show that the Cobb-Douglas model provides better fits and estimators consistent with theoretical principles. Similarly, it is shown that the use and effect of each production factor on the yield of rainfed white corn is different between the regions of the country, so it was shown that public policy actions should be differentiated based on the needs and particularities of each region. An analysis of the effect of each input at the regional level and a discussion of the possible effects of some support programs for the agricultural sector focused on a particular input are presented.